Correction: Association between cancer stigma and cervical cancer screening uptake among women of Dhulikhel and Banepa, Nepal. - Bandana Paneru; Aerona Karmacharya; Alina Bharati; Soniya Makaju; Bikram Adhikari; Dikshya Kafle; Sunila Shakya; Spiegelman Donna; Sangini Seth; Anne Stangl; Aamod Dhoj Shrestha; Archana Shrestha (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0285771.].